LOTE (Languages Other than English) learners’ investment in learning languages - Lu, Juexuan; He, Lifen; Shen, Qi (Círculo de Lingüística Aplicada a la Comunicación, 2020)
This study draws on the model of language learning investment to explore China’s LOTE (Languages Other than English) students’ learning motivation. Data collected through in-depth interviews with 35 university students were analyzed in an inductive way. The findings show that: (1) the participants invested in learning LOTEs because they had enough affordances (resources applicable to LOTE learning) and/or perceived target language-related benefits (economic, cultural or social ones) from LOTE learning, even though most of our participants were initially involuntary applicants; (2) students were reluctant to invest in learning their target language(s) and merely strove to fulfil their program(s) when they were lacking affordances, perceiving few benefits, or even devalued by the in-context ideologies. These findings provide important implications for LOTE educators to motivate their students, and for policy makers to improve China’s LOTE education.